Physicochemical Properties of Tomato Paste Fortified Functional Cheddar Cheese - Putri Ramadhany; Anastasia Prima Kristijarti; Graciella Lorenz Susanto; Geraldo Prajna (University of Sultan Ageng Tirtayasa, 2023)
The aim of this research is to fortify cheddar cheese’s nutritional value by adding tomato paste. This study transformed ultra-heat treatment (UHT) milk into cheese through cheddaring. Tomato paste was added at 5 g/L, 10 g/L, and 15 g/L during the first curd formation, together with calcium chloride (CaCl2). The type of rennet (animal and microbial) was varied at 0.25 ml/L of milk. Ripening was done in one month at 4°C. According to this study, animal rennet formed curd better than microbial rennet. The addition of tomato paste slightly decreases the curd formation, with approximately 0.37 % reduction per 5 gram of tomato paste. Increasing tomato paste to 15 g/L would increase lycopene to 0.993 – 0.996 mg/100 g. The cheese produced was categorized as extra-hard and low-fat based on the percentage of Moisture Non-Fat Basis (MNFS) and Fat on Dry Matter (FDM). The addition of tomato paste reduced the pH value, resulting in increased firmness and hardness and decreased chewiness and springiness.